2020
DOI: 10.1186/s13073-020-00812-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide profiles of circular RNA and RNA-binding protein interactions reveal effects on circular RNA biogenesis and cancer pathway expression

Abstract: Background Circular RNAs (circRNAs) are stable, often highly expressed RNA transcripts with potential to modulate other regulatory RNAs. A few circRNAs have been shown to bind RNA-binding proteins (RBPs); however, little is known about the prevalence and distribution of these interactions in different biological contexts. Methods We conduct an extensive screen of circRNA-RBP interactions in the ENCODE cell lines HepG2 and K562. We profile circRNAs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 83 publications
2
90
0
Order By: Relevance
“…However, the patterns of circRNA-protein interactions are more complex and interesting than those of circRNA-miRNA interactions and have been the subject of great focus recently 50 . RBPs affect all phases of the circRNA lifecycle, including circRNA biogenesis, localization, function and degradation 51 . Herein, we determined that increased expression of circRHOBTB3 restrains PTBP1 expression by binding to HuR and facilitating its ubiquitination and degradation, which consequently restrains CRC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patterns of circRNA-protein interactions are more complex and interesting than those of circRNA-miRNA interactions and have been the subject of great focus recently 50 . RBPs affect all phases of the circRNA lifecycle, including circRNA biogenesis, localization, function and degradation 51 . Herein, we determined that increased expression of circRHOBTB3 restrains PTBP1 expression by binding to HuR and facilitating its ubiquitination and degradation, which consequently restrains CRC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an extensive screening of circRNA-RBP interactions has been performed, with the aim of obtaining a broader picture of the circRNA-RBP interactome [ 58 ]. A comprehensive catalogue of circRNA-RBP interactions in HepG2 and K562 cells was generated, and several candidates have been characterized [ 58 ]. In particular, it was demonstrated that circCDYL associates to IGF2BP1 and IGF2BP2, and that this interaction modulates proliferation of bladder cancer cells.…”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
“…In particular, it was demonstrated that circCDYL associates to IGF2BP1 and IGF2BP2, and that this interaction modulates proliferation of bladder cancer cells. Indeed, the inhibition of circCDYL perturbs the expression of key cancer genes, and elevated levels of circCDYL are linked to the overall survival of bladder cancer patients [ 58 ].…”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
“…Notably, numerous circRNAs that do not possess miRNA-binding sites still have a wide range of biological functions, indicating that circRNAs have their own additional regulatory functions. Previous studies have revealed that circRNAs may interact with RBPs or other proteins to form circRNA-protein complexes, which may impact the function and mechanisms of action of binding proteins ( 62 , 63 ). For example, circ-FOKX2 may integrate with Y-box binding protein 1 and heterogeneous nuclear ribonucleoprotein K to facilitate the upregulation of the oncogenes NUF2 and pyridoxal kinase, ultimately accelerating pancreatic ductal adenocarcinoma progression ( 64 ).…”
Section: Brief Overview Of Circrnasmentioning
confidence: 99%